2014
DOI: 10.18632/oncotarget.2795
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial translocation and interaction of cofilin and Drp1 are required for erucin-induced mitochondrial fission and apoptosis

Abstract: Cofilin is a member of the actin-depolymerizing factor (ADF) family protein, which plays an essential role in regulation of the mitochondrial apoptosis. It remains unclear how cofilin regulates the mitochondrial apoptosis. Here, we report for the first time that natural compound 4-methylthiobutyl isothiocyanate (erucin) found in consumable cruciferous vegetables induces mitochondrial fission and apoptosis in human breast cancer cells through the mitochondrial translocation of cofilin. Importantly, cofilin regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 52 publications
2
50
1
Order By: Relevance
“…Recent works found that mitochondrial translocation of Drp1 were dependent on ROCK activation [39], and ROCK mediated mitochondrial fission by promoting dynamin-related protein-1 (Drp1) recruitment to the mitochondria [14]. These findings suggest that ROCK inhibitor Y-27632 should be a type of mitochondrial fission inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works found that mitochondrial translocation of Drp1 were dependent on ROCK activation [39], and ROCK mediated mitochondrial fission by promoting dynamin-related protein-1 (Drp1) recruitment to the mitochondria [14]. These findings suggest that ROCK inhibitor Y-27632 should be a type of mitochondrial fission inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…5a). ROCK1 activation is reportedly involved in the regulation of mitochondrial translocation of Drp1 and mitochondrial fission through its dephosphorylation at Ser 637 in human breast cancer cells 19 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Once Drp1 is activated, it translocates from the cytosol to the outer mitochondrial membrane and forms a ring structure around the mitochondria, resulting in fission of mitochondria followed by Cyto C release and caspase activation, eventually leading to apoptosis 38 . Additionally, dephosphorylation/activation of Drp1 at Ser 637 in human has been showed to promote its translocation from the cytosol to mitochondria and mitochondrial fission 19,29,39,40 . Consistent with these reports, our data revealed that dephosphorylated Drp1 at Ser 656/600 (rat/mouse) (corresponding to Ser 637 in human Drp1 isoform 1) increased mitochondrial translocation of Drp1 and leads to mitochondrial fission and nerve cell apoptosis in both in vitro and in vivo models of PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations